Reflections on Shopping Trolley secrets: A case study on public engagement in digital footprint data research - James, Alice; Skatova, Anya; Burgess, Romana; Poon, Neo; Fryer, Laura; Suhag, Alisha; Daly, Joe; Della Nave, Helen (International Journal of Population Data Science, 2025)
Introduction & Background Shopping Trolley Secrets was an interactive public engagement space that took place at We The Curious Science Centre (WTC) aimed at fostering meaningful conversations and gathering feedback on shopping data use for health research. There are a number of ways the space facilitated this communication, including a postcard writing station (written feedback), interactive polls (iPad survey and string board survey), interactive shopping experience activities and in-person discussions (meet the researcher events). Objectives & Approach This paper aims to provide a case study for public engagement in digital footprint data research. The paper outlines the processes undertaken in the design and implementation of the project as well as reflections from staff at both University of Bristol Digital Footprints Lab and WTC on impacts this initiative has had on their approach to public engagement in research going forward. Relevance to Digital Footprints This paper is relevant to Digital Footprints as public engagement has been identified as a key aspect in increasing social acceptability in the use of digital footprint data for research. Innovative approaches to public engagement are important to share with the digital footprint community so learnings can be applied to future work in this area. Results This paper outlines barriers and facilitators encountered by the research team at University of Bristol and staff at WTC. The process of conceptualising and undertaking the events are outlined in detail along with reflections on the process from staff from both organisations. The impacts of the public engagement activities on our work are also laid out including funding opportunities and a shopping data visualisation tool. Conclusions & Implications This paper has implications for future research in the digital footprints space, it highlights the benefits of innovative public engagement in digital footprints research to both research staff, corporate partners and for public good.